2013
DOI: 10.1136/bmjopen-2013-003314
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and asthma control in patients with severe asthma

Abstract: ObjectivesWe hypothesised that severe asthmatics taking a statin drug, in addition to inhaled corticosteroids/long-acting β-agonist inhaler therapy, would have better asthma symptom control and improved lung function compared to their controls.Study designA retrospective, cross-sectional study of 165 patients with severe asthma seen from 2001–2008. Hierarchical linear and logistic regression models were used for modelling fitting.SettingUniversity of California, Davis Medical Center (Sacramento, California, US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 37 publications
2
40
1
Order By: Relevance
“…Moreover, a recent study has identified higher adjusted mean ACT scores in severe asthmatics with the use of statins [4]. In contrast, these findings were not supported by others [2,17,18].…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Moreover, a recent study has identified higher adjusted mean ACT scores in severe asthmatics with the use of statins [4]. In contrast, these findings were not supported by others [2,17,18].…”
Section: Discussioncontrasting
confidence: 55%
“…Inhibition of airway remodelling which is secondary to airway smooth muscle proliferation and contraction, goblet cell hyperplasia and blockage of inflammatory cell influx with depleted cytokines release are the most significant effects of statins on asthmatic airways [4]. According to Kwak et al, diminished amounts of eosinophils and macrophages after statin treatment are the proof of decreased airway inflammation [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a systematic review concluded that although statins had an anti-inflammatory effect in asthma, they did not significantly affect lung function or symptoms [228]. On the other hand, a recent retrospective review of obese patients with severe asthma showed that receiving statins was associated with better symptom control, suggesting a role for statins in this specific asthma phenotype [229]. The effects of statins on inflammation and remodelling have been studied mainly using simvastatin in animal models of allergic asthma.…”
Section: Statins Metformin and Vitamin Dmentioning
confidence: 98%
“…This work provides indirect evidence that statins may improve important asthma outcomes such as acute exacerbations. This work along with others 24 provides support for a large randomized controlled trial (RCT) of a statin intervention in asthma.…”
Section: Statin Use and Asthma Outcomes: Findings Limitations And Omentioning
confidence: 56%